Imperative Remarks for “On Common Coupled Fixed Point Theorems for Comparable Mappings in Ordered Partially Metric Spaces” and an Answer to the Question: How to Smooth It Away - Hamed H. Alsulami; Erdal Karapınar; Antonio Francisco Roldán Lόpez de Hierro (Abstract and Applied Analysis)
We show that the main result in the work by Mutlu et al. is not true. We explain point by point some of its main mistakes and we propose an alternative version to smooth away the defects of it.